Estrategias de comunicación visual para la difusión sobre la drogadicción en jóvenes de la ciudad de Ambato” - Guachamboza Toainga, Bryan Joel (2024)
This project has investigated possible causes and consequences of drug addiction hitting the city of Tungurahua province. For this reason, this province has one of the highest drug addiction rates in the country. It is based on the implementation of a communication strategy aimed at informing young people about the problems associated with the consumption of these substances. In addition, it is worth evaluating young people who are more involved in this practice, conducting research using qualitative and quantitative methods to understand the real situation. Family, mental health and addiction problems in high tolerance consumption of psychotropic substances by adolescents confirm the need for the campaign to resolve the issue of prevention and information is complementary to resolve this problem. Contribution from psychology experts, advertising and audiovisual graphic designers. That is, topics of awareness campaigns and visual communication strategies are addressed.